A yellow-green tetranuclear Cd(II) (8-quinolinolato) chelate with thiophene group: synthesis, crystal structure, photophysical properties and DNA binding. Issue 23 (10th June 2015) - Yang, Baixing; Huo, Yanping; Zhang, Liming; Hu, Sheng; Wang, Songying; Huang, Baohua
Abstract: One novel tetranuclear Cd(II) complex with formula [Cd4 L6 (NO3 )2 ] (1 ) is accessible by solvothermal reaction of Cd(NO3 )2 with a ( E )-2-[2-(3-thienyl)ethenyl]-8-quinolinol ligand (HL ), which was characterized by means of 1 H NMR, ESI-MS, elemental analysis, IR and TGA. X-ray structural analysis indicated that1 exhibited a double open cubane-like core structure, which was bridged by six 8-hydroxyquinolinate-based ligand. Rich aromatic stacking interactions and non-classical C–H···O weak interactions sustain the packing structure. The coordination behavior of cadmium salt andHL in solutions was performed by UV–vis and photoluminescence (PL). The experimental results corroborate that emission spectrum of the title complex in the solid state at room temperature gives strong yellow-green luminescence. In addition, the thermal stability, fluorescent lifetime, electronic calculation and quenching behaviors of C60 and EtBr-DNA interacted with the compound were also investigated. Graphical abstract: